2020
DOI: 10.1109/access.2020.3020906
|View full text |Cite
|
Sign up to set email alerts
|

A Fault Diagnosis Method Based on Improved Adaptive Filtering and Joint Distribution Adaptation

Abstract: In the real environment of industrial equipment, the vibration signals of essential components show deviations due to the fault and noise. Notably, the noise in the signal will interfere with the diagnosis process of the signal and reduce the accuracy of fault diagnosis. Based on the above problem, adaptive filtering (AF) is used as an excellent method to attenuate noise without specifying the noise type. However, how to define the most appropriate length and type of morphological filter element is the most in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 40 publications
0
10
0
1
Order By: Relevance
“…We compare the transfer results and transfer performances of the presented method with those state-of-the-art machine learning methods including CNN, transfer component analysis (TCA), joint distribution adaptation (JDA) [31], geodesic flow kernel (GFK) [32], deep domain confusion (DDC), deep adaptation network (DAN) and DTN with DDA. For comparison, the structural parameters of CNN are the same as DTN.…”
Section: ) Comparisons With Other Methodsmentioning
confidence: 99%
“…We compare the transfer results and transfer performances of the presented method with those state-of-the-art machine learning methods including CNN, transfer component analysis (TCA), joint distribution adaptation (JDA) [31], geodesic flow kernel (GFK) [32], deep domain confusion (DDC), deep adaptation network (DAN) and DTN with DDA. For comparison, the structural parameters of CNN are the same as DTN.…”
Section: ) Comparisons With Other Methodsmentioning
confidence: 99%
“…The training and transfer methods are consistent with the proposed method. Two deep transfer learning methods are selected: the Transfer Component Analysis (TCA) [32] and the Joint Distribution Adaptation (JDA) [33]. To further demonstrate the effectiveness of classification, the dataset is used to test all models.…”
Section: ) Different Degree Of Failurementioning
confidence: 99%
“…Han et al [21] introduced the joint distribution adaptation (JDA) into a deep transfer network (DTN) to avoid negative adaptation and presented smooth convergence for fault diagnosis in industry applications. The discussion in [12] showed that joint distribution adaptation may obtain better performance in fault diagnosis by reweighting the source instance on the basis of its correlation with the target instance to reduce the cross-domain feature distribution discrepancy [22,23]. Chen et al [23] developed an unsupervised domain adaptation approach to reduce the domain shifts between the data gathered from the experimental platform and the operating platform of the rotating machine by aligning the features extracted from the two data domains.…”
Section: Introductionmentioning
confidence: 99%
“…Many existing DA approaches usually aim to reduce the difference of cross-domain feature distributions, e.g., the distribution adaptation, the instance reweighting, or joint matching (join the distribution adaptation and instance reweighting). The distribution adaptation approaches [ 12 , 13 , 14 ] mainly include marginal adaptation (MDA) [ 15 , 16 , 17 , 18 , 19 ], conditional adaptation (CDA) [ 20 ], or both [ 12 , 21 ] and are applied for most distribution adaptation approaches. Lu et al [ 15 ] adapted the marginal distribution by MMD to minimize the distribution discrepancy across domains and introduced MMD into a deep neural network (DNN).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation